KERJA SAMA INDONESIA DAN SPACEX DALAM MEWUJUDKAN KEMANDIRIAN KEANTARIKSAAN - Nofriandy, M. Annas; Saeri, Mohammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Space cooperation has become one of the strategic forms of collaboration widely undertaken by countries around the world. As a developing nation, Indonesia has been involved in space cooperation since 1967. To date, Indonesia has partnered with various actors to launch its satellites into Earth’s orbit. In recent years, there has been a growing tendency to cooperate with one particular international actor—SpaceX—for satellite launches. This study examines the reasons and objectives behind Indonesia’s cooperation with SpaceX and explores why Indonesia has opted not to collaborate with other satellite launch service providers. This research employs a qualitative methodology with document analysis as the primary data collection technique. The study analyses various documents, including government reports, academic journals, publications from international organizations, news articles, and policy documents related to space cooperation. The analysis focuses on international cooperation, satellite launch collaboration, technology development, satellite management, and communication network enhancement. Based on the success of multiple satellite launches and the introduction of satellite internet capable of reaching remote areas, it can be concluded that Indonesia’s collaboration with SpaceX is primarily driven by the technological reliability offered by the company. This partnership not only provides effective and timely access to space but also represents a strategic move that brings Indonesia closer to achieving its national space autonomy. By leveraging SpaceX’s advanced capabilities, Indonesia gains both operational benefits and long-term momentum in developing its independent space infrastructure. Collaboration with SpaceX offers lower costs compared to competitors while enabling the deployment of larger payloads. Beyond rocket launches, the partnership in satellite internet technology has also supported the advancement of Indonesia’s digital ecosystem by significantly reducing connectivity blind spots. This research highlights that international cooperation in the space sector can play a crucial role in driving national progress and innovation. Keywords: SpaceX, Space Cooperation, Starlink, Indonesia, Satellite, Rocke